The Effect of Using Pain Management Techniques in the Rehabilitation of Chronic Lower Back Injury in Athletes and Non-Athletes - Haider Jumaah Asree Ktaiman (Journal of Global Pharma Technology, 2018)
In the past few days increased chronic lower back pain, where today is a disease of the era due to the high effort and continuous and disproportionate exercise of the athlete and loads of low back, and the fact that chronic lower back pain is a disease of the modern era and through the experience and work of researchers in medicine Physical therapy and physiotherapy have found that there is little or no use of pain management techniques to treat chronic low back pain and that chronic low back pain is a disease of the modern age. Therefore, researchers considered this study as the first study in Iraq in terms of Techniques in pain management to treat chronic lower back pain. The researchers used the experimental method was the sample included the 12 players injured who suffer from the bottom of the chronic back pain represented by convulsions and muscle cramps, chronic where formed the experimental group of 6 players used pain management techniques within the program consists of 16 weeks either the control group used its traditional 16 week. Search Results showed superiority of the experimental group on the control group in the test Schober to measure the degree of pain where he showed differences (0.021 (in the test side flexibility differences emerged (0.01).Keyword: Pain management techniques, Rehabilitation, Lower back injury.